Speak Up! 2024 for Malaysian Heroes confidence booster - Nor Yazi, Khamis; Wan Noor Farah, Wan Shamsuddin; Azwin Arif, Abdul Rahim; Nur Syafawati, Sabuan; Suriayati, Mohd Sidek (Corporate Communication Division, 2024)
GAMBANG, 20 September 2024 – The 2024 Speak Up! event, now in its fifth edition, marked yet another successful collaboration between the Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) and the Malaysian Armed Forces.